DETERMINAN AKUNTABILITAS KINERJA SEKOLAH MENENGAH NEGERI SE-PULAU LOMBOK - Humaidi Humaidi; Endar Pituringsih; Muh Irwan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2017)
This study aims to test and to find empirical evidence about the effect of clarity goal budgeting, budgeting participation, reporting and accounting control system to the accountability performance of the public high schools throughout the Lombok Island. The method used is associative research. The total population are 262 public high schools. To determine the number of population samples used the formula Slovin with standard error of 10% in order to obtain a sample size of 72. Respondents were recruited in this study are development school teams and school stakeholders. The analytical tool used in the study were multiple linear regression, the unit of analysis in this study are state secondary school (junior high school, senior high school, and vocational school) throughout the Lombokisland. The results of this study showed that the goal clarity budgeting, budgeting participation, reporting and accounting control and simultaneous partial effect on performance accountability of state secondary schools throughout the Lombok Island. This study may provide information to stakeholders (government and public) to evaluate and to do the monitoring function process of accountability and transparency of state budgets secondary schools throughout the Lombok Island